Charlie Brown's 'Cyclopedia, v.15 : featuring electricity and magnetism. - Schulz, Charles (New York : Funk and wagnalls, 1980)
Super Questions and answers and amazing facts
"Based on the Charles M. Schulz Characters"--Snoopy
Keywords: Cyclopedias; Energy -- Juvenile literature